KEBERAGAMAN MASYARAKAT DALAM TEKS GARAP LAKON BRAMBANG ULUNG: STUDI WAYANG SASAK - Habiburrahman, Lalu (Universitas Hamzanwadi, 2024)
This research is entitled Genetic Diversity in Working on Sasak Wayang Plays. This research uses strategy theory. Theoretical point of view using puppet strategy. The research method used from this point of view is the field research method. Data analysis uses narrative methods. This research found the emergence of the concept: Widi, Hyang Widi, Sang Hyang Widi or Sang Hyang Wiwakasan in wayang performances. Analysis uncovered a loan concept from Hindu beliefs. This concept is the concept of God in the dhalang-dhalang religion of the early Sasak wayang era. It's like: I Nengah Goang and I Nengah Giur. Further analysis found that these two dhalangs, which were popular in their Sasak era, had musicians from the Kumbung area. The Kumbung area is close to where work on the wayang play Brambang Ulung is taking place. Apart from that, the Penenteng Aik area where the work on the play took place also neighbors Hindu communities such as in Kraning and in Ubung. Data analysis concludes that the emergence of Hindu concepts in wayang sasak performances due to structural factors through the influence of popular dhalangs from the early era but is not rejected culturally due to the geographical proximity of the response hamlet, which is predominantly Muslim, to neighboring hamlets nearby, which are Hindu communities.